Analisis Manajemen Kurikulum Merdeka Pada Smks Kristen Bk Maranatha Kecamatan Dolo Provinsi Sulawesi Tengah - Rudin M; Maria Lea Frensy Bakarbessy (Postgraduate, University of Mataram, 2025)
Curriculum management involves planning, organizing, implementing, and evaluating to achieve effective educational goals. This curriculum provides freedom to students and teachers in the learning process, with a focus on developing individual learning potential and interests. This is an innovative approach that encourages creativity and flexibility in education. This type of research is qualitative research with five informants selected. Data collection uses observation, interview and documentation techniques. The data analysis techniques used are: 1) Data collection, 2) Data Reduction, 3) Data Presentation, 4) Verification, 5) Conclusion. The indicators used to measure Management are: planning, implementation and supervision. Based on the results of research and analysis conducted by the researcher, it can be concluded that 1) Independent Curriculum Management at SMKS in Central Sulawesi Province can be said to have not been implemented properly. 2) Inhibiting factors in Independent Learning Curriculum Management: a) Budget Limitations, b) Budget Uncertainty, c) Regulation and Bureaucracy, d) Poor Facility Conditions, e) Limited Human Resources. 3) Supporting factors for the Independent Curriculum in Central Sulawesi Province are as follows: a) Availability of Adequate Funds, b) Timeliness of Fund Distribution, c) Transparency and Accountability, d) Government and Stakeholder Support, e) Adequate Infrastructure.